Magnetic Bionanoparticle Enhances Homing of Endothelial Progenitor Cells in Mouse Hindlimb Ischemia - Kang, Hyun-Jae; Kim, Ju-Young; Lee, Ho-Jae; Kim, Keum-Hyun; Kim, Tae-Youn; Lee, Choon-Soo; Lee, Hyun-Chae; Park, Tai Hyun; Kim, Hyo-Soo; Park, Young-Bae (Korean circulation journal, 2012)
Poor homing efficiency is one of the major limitations of current stem cell therapy. Magnetic bionanoparticles (MPs) obtained from Magnetospirillum sp. AMB-1 have a lipid bilayer membrane and ferromagnetic properties. We evaluated a novel priming strategy using MPs to enhance the homing of transplanted progenitor cells to target tissue. Effects of MP on proliferation, viability, and migration of late human endothelial progenitor cells (EPCs) were examined in vitro. Additionally, effects of MP on gene and protein expression related to survival and adhesion were evaluated. Homing and angiogenic efficiency of MP transferred late EPCs was evaluated in nude mouse hindlimb ischemia model. Below threshold concentration, MP transfer did not influence proliferation or survival of late EPCs, but enhanced migration and trans-endothelial migration of late EPCs toward magnet. Below threshold concentration, MP transfer did not influence gene and protein expression related to survival. In the mouse hindlimb ischemia model, late EPCs treated with high dose MP (5 ug/mL) showed enhanced homing of injected late EPCs in the ischemic limb by magnet, compared to low dose MP (1 ug/mL) treated late EPCs. In addition, high dose MP transferred EPC showed significantly better improvement of perfusion in ischemic limb compared to untreated EPC. MP transfer with magnet application can be a promising novel strategy to enhance homing efficacy and outcomes of current stem cell therapy.